2022
DOI: 10.7554/elife.66646
|View full text |Cite
|
Sign up to set email alerts
|

A novel gene ZNF862 causes hereditary gingival fibromatosis

Abstract: Hereditary gingival fibromatosis (HGF) is the most common genetic form of gingival fibromatosis which is featured as a localized or generalized overgrowth of gingivae. Currently two genes (SOS1 and REST), as well as four loci (2p22.1, 2p23.3-p22.3, 5q13-q22, and 11p15), have been identified as associated with HGF in a dominant inheritance pattern. Here we report thirteen individuals with autosomal-dominant HGF from a four-generation Chinese family. Whole-exome sequencing followed by further genetic co-segregat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…18 Although ZNF862 function is not clearly known, the functional study reported by the authors supports the biological role of ZNF862 in increasing the synthesis of profibrotic factors, particularly COL1A1 (collagen type I alpha 1 chain). 18 The aim of the present study was to apply WES to identify the genetic mutations associated with members of four families with clinical diagnosis of HGF. The genetic analysis led to identification of two new variants in known HGF genes (REST and SOS1) and two mutations in new HGF genes, including ALK (ALK receptor tyrosine kinase) and CD36 (collagen type I receptor and thrombospondin receptor).…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…18 Although ZNF862 function is not clearly known, the functional study reported by the authors supports the biological role of ZNF862 in increasing the synthesis of profibrotic factors, particularly COL1A1 (collagen type I alpha 1 chain). 18 The aim of the present study was to apply WES to identify the genetic mutations associated with members of four families with clinical diagnosis of HGF. The genetic analysis led to identification of two new variants in known HGF genes (REST and SOS1) and two mutations in new HGF genes, including ALK (ALK receptor tyrosine kinase) and CD36 (collagen type I receptor and thrombospondin receptor).…”
Section: Introductionmentioning
confidence: 70%
“…characterized two novel REST mutations (c.2449C > T, p.R817* and c.2771_2793dup, p.E932Kfs*3) in Chinese families with HGF. More recently, a missense mutation in the zinc finger protein 862 gene ( ZNF862 ), located on chromosome 7q36.1, was reported in 13 individuals with autosomal‐dominant HGF in a four‐generation Chinese family 18 . Although ZNF862 function is not clearly known, the functional study reported by the authors supports the biological role of ZNF862 in increasing the synthesis of profibrotic factors, particularly COL1A1 (collagen type I alpha 1 chain) 18 …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Besides, the son of sevenless-1 gene (SOS1, GINGF1) [42] and the RE1-silencing transcription factor gene (REST, GINGF5)[46, 47] were clearly associated with the occurrence of HGF [48,49]. Moreover, ALK, CD36, and ZNF862 (zinc nger protein 862) are new genes found recently, which are also associated with HGF [50,51]. Histologically, HGF is characterized by proliferative brous overgrowth of the gingival tissues and causes enlargement of the attached gingival tissue [7].…”
Section: Discussionmentioning
confidence: 99%
“…7 In our previous study, we found the mutation of ZNF862 (c.2812G > A) was associated with a Chinese family. 8 However, the biological function of the ZNF862 was unknown and the related experiment evidence was absent.…”
Section: Introductionmentioning
confidence: 99%